Contributions of the University Extension in Environmental Education for the Management of Solid Waste in the UFCG - CAmpus Pomba - Nogueira Medeiros, Amanda; Gualberto de Andrade Sobrinho, Luiz; Rocha Neto, Olavio; Dantas Leite, Iris Rebeca; da Silva Medeiros, José Ludemário; Tiburtino Brasil, Jesus Carlos; da Silva, Elisângela Maria (Guará Journal, 2018)
The  article  reports  the  Extension  Project  carried  out, through  environ-mental  education,  that  aimed  to encourage  a  change  of  thought  and  behavior  in order  to  promote  sustainable  attitudes  about  the problem  of  generation  and  environmentally adequate disposal  of  solid  waste  generated by students of the first graduation period Of the Federal University of Campina Grande - Campus of Pombal. The project involved 16 (sixteen) classes of incoming students from the Agronomy, Environmen-tal Engineering,  Civil Engineering  and  Food  Engineering courses  of  the CCTA/UFCG Pombal Campus, corresponding to 378 (three hundred and seventy-eight) students who attended the lectures on “Solid Waste Man-agement” and  answered  the  questionnaires consisting  of  20 (twenty)  questions. The execution of the project, in its two years, was fundamental  to  bring the  academic community  closer  to  the  reality  of  the problems involved in the issue of solid waste management.
Keywords: Sustainability; Recycling; Questionnaires; Engineering